Emotional inteligence of university professors: a comparative study between brazilian public and private sector education - Dornelles, Marcos; Crispim, Sergio Feliciano (Universidade Estadual de Campinas, 2020)
The current context of Brazilian higher education favors the workload of teachers, due, among other factors, to the increase in the proportion of students per teacher. In addition, the current instability in public policies in education tends to add other factors that may impact both classroom performance and teachers' quality of life differently in public and private education. Emotional intelligence has attracted growing interest from academia, and it is well known that it can enable better performance at work, better shielding from possible harmful effects of the professional environment and better quality of life. Given its importance, this study aimed to verify whether there are significant differences in levels of emotional intelligence among public and private higher education teachers in Brazil. For this, the Wong and Law (2002) scale was used to measure the level of emotional intelligence in four distinct dimensions with a sample of 415 individuals. Research has identified that teachers working in private universities have a higher level of emotional intelligence and suggests professional training in emotional intelligence to mitigate some harmful effects of the environment on their well-being and teaching process.